Residual strength of granitic rocks: interplay between GSI and confining pressure - Samad Narimani; Seyed Mortaza Davarpanah; Ákos Török; Balázs Vásárhelyi (Scientific Reports)
Abstract Residual strength is an important factor in rock mechanics and geotechnical engineering, referring to the remaining strength of rocks following considerable deformation or damage. This study investigates the post-failure behavior of granitic rock samples from Bátaapáti, Hungary, using multiple failure triaxial testing and residual strength models. Experimental results show that residual strength is significantly influenced by confining pressure, with values increasing as confinement rises. Key models, including the Hoek-Brown failure criterion, Geological Strength Index (GSI), Residual Strength Index (RSI), and Cohesion-Loss approaches, were evaluated for their ability to predict residual strength. Nonlinear regression of deviator stress versus confining pressure was found. Using this nonlinear model, the relationship between the residual GSI and the confining pressure could be determined. It was carried out that the increasing the confining pressure the residual GSI logarithmically increased. It means, the residual GSI is not a material constant.